2011
DOI: 10.1016/j.bbrc.2010.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic phosphatidic acid influences the expression and regulation of cyclic nucleotide phosphodiesterase 3B and lipolysis in 3T3-L1 cells

Abstract: Cyclic phosphatidic acid (cPA) is found in cells from slime mold to humans and has a largely unknown function. We previously reported that cPA significantly inhibited the lipid accumulation in 3T3-L1 adipocytes through inhibition of PPARγ activation. We find here that cPA reduced intracellular triglyceride levels and inhibited the phosphodiesterase 3B (PDE3B) expression in 3T3-L1 adipocytes. PPARγ activation in adipogenesis that can be blocked by treatment with cPA then participates in adipocyte function throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, the mechanism through which PDE3B is involved in intracellular cAMP production in response to cPA has remained unclear. We conducted this study on colon cancer cells using cPA, which had been shown previously to increase intracellular cAMP levels directly [8], a function of cPA that is also suggested by the anti-invasive properties of cPA [9]. We found that cPA inhibited the growth of HT-29 and LOVO cells, which express high levels of PDE3B, but not the growth of DLD-1 and Caco-2 cells, which express low levels of PDE3B.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…However, the mechanism through which PDE3B is involved in intracellular cAMP production in response to cPA has remained unclear. We conducted this study on colon cancer cells using cPA, which had been shown previously to increase intracellular cAMP levels directly [8], a function of cPA that is also suggested by the anti-invasive properties of cPA [9]. We found that cPA inhibited the growth of HT-29 and LOVO cells, which express high levels of PDE3B, but not the growth of DLD-1 and Caco-2 cells, which express low levels of PDE3B.…”
Section: Discussionmentioning
confidence: 80%
“…We found that cPA inhibited the proliferation of HT-29 and LOVO cells but not of DLD-1 and Caco-2 cells (Figure 3A), which have lower endogenous levels of PDE3B than HT-29 and LOVO cells [8]. To test whether PDE3B affects the proliferation of HT-29 cells, PDE3B expression was knocked down using siRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CPA directly binds to PPARγ with nanomolar affinity and stabilizes the binding of a corepressor, silencing mediator of retinoid and thyroid hormone receptors (SMRT), to PPARγ — resulting in inhibition of PPARγ-related gene expression5152. CPA also inhibits phosphodiesterase 3B (PDE3B) expression and subsequently increases cAMP, leading to increased lipolysis in 3T3-L1 cells and an inhibition of adipogenesis53. Even though both PLD1 and PLD2 hydrolyze PC to produce PA, PLD1 is not involved in insulin-stimulated CPA production52.…”
Section: Discussionmentioning
confidence: 99%